TINJAUAN YURIDIS TERHADAP SIKAP PEMERINTAH DI TENGAH WABAH COVID 19 DITINJAU DARI UU NOMOR 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA (Jurnal Konstituen, 2020)
This paper describes a juridical review of the government’s attitude in dealing with the Covid 19 plague in terms of Articles Number 39 of 1999 concerning Human Rights. In this case the economic protection of the people affected by the economy. This is the duty of the state in pursuing all forms of policies and budgets in implementing guarantees regarding protection (to protect), respect (to respect), and fulϔillment (to fulfill) of basic human rights, especially the right to life and the right to health inherent to its citizens as mandated by the Universal Declaration of Human Rights in 1948, the 1945 Constitution of the Republic of Indonesia, Law No. 39 of 1999 concerning Human Rights, and Law 39 of 2009 concerning Health. This scientiϔic paper uses a normative research method using the statutory approach. It should be highlighted in the implementation of the policies determined in the face of the covid outbreak 19 namely in its implementation by not ignoring a series of community rights such as the right to obtain basic health services according to medical needs, food needs, and other daily necessities during the establishment of the policy.Keywords: juridical review, attitude, government, plague, covid 19, human rights